The impact resistance and mechanical properties of concrete reinforced with waste polypropylene carpet fibres - Mohammadhosseini, Hossein; Abdul Awal, A.S.M.; Mohd Yatim, Jamaludin (Elsevier, 2017)
The utilization of waste materials is one of the fundamental issues of waste management strategies in many parts of the world. With the advances in cement and concrete technology, the use of waste materials in the concrete industry has developed gradually widespread because of technological, economic and ecological advantages. This paper presents the potential use of waste polypropylene carpet fibres, and highlights the impact resistance and mechanical properties of concrete with the fibres. Six volume fractions varying from 0 to 1.25% of 20-mm-long carpet fibres were used with ordinary Portland cement (OPC) concrete mixes. Another six mixes were made where OPC was replaced by 20% palm oil fuel ash (POFA) as supplementary cementing material. It has been found that the addition of polypropylene carpet fibre decreased the slump values and increased the VeBe time of fresh concrete. The inclusion of carpet fibre to either OPC or POFA concrete mixes did not improve the compressive strength at early ages. At later ages, however, the compressive strength of the mixtures containing POFA significantly increased and the obtained values were higher than that mixes with OPC alone. The positive interaction between carpet fibres and POFA leads to high tensile strength, flexural strengths and impact resistance, thereby increasing the concrete ductility with higher energy absorption and improved crack distribution. It is concluded that waste carpet fibres and palm oil fuel ash can be used as building materials in the construction of sustainable concrete.